Design of 28 nm FD-SOI CMOS laser drive circuit for energy efficient Datacom applications - Giannakopoulos, Stavros (My University, 2015)
The field of power efficient optical communications has seen a large growth in the recent years due to the growing number of data-centers around the globe and the increasing demands for data rate. While the performance of those data links keeps increasing, it drives the power consumption high as well. Research in the field of energy efficient optoelectronic links is picking up speed in order to keep up with the current trends in data-rate demand without exceeding the power budget. At higher speeds, the electronics start to have more crucial role in the power consumption, therefore, the work of optimizing a optical link starts from the transmitter and receiver electronics. This study attempts to explore the design of an existing 65 nm CMOS transmitter circuit and transfer it to the 28 nm FDSOI CMOS process in order to benefit from the intrinsic power efficiency and speed provided by technology scaling. A laser driver circuit is designed using PAM-4 modulation, optimized to drive a VCSEL laser at 25GHz frequency. Additional techniques are implemented to provide control over the output behavior of the chip in real time, allowing for a great range of experimental scenarios to be performed with a single chip and to potentially permit the testing of different VCSEL diodes. The benchmarked values of the original 65 nm design are met and surpassed by the 28 nm simulated values, even though the latter is constructed with several degrees of parametrization available, in order to serve as a testing chip. The simulated results also surpassed in terms of energy efficiency, most the top-tech driver circuits in the literature.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology